2020
DOI: 10.1177/0040517520928792
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and multilevel fuzzy comprehensive predicting comfort parameters of soft materials by a new handle evaluation system

Abstract: In this paper, a multilevel fuzzy comprehensive evaluation (FCE) model consisting of tactile comfort and four primary handle characteristics (FPHCs) is developed. The physiological perceptions of 30 home textile fabrics were predicted, to verify the practicability of the FCE model and the reliability of the objective measurement based on the self-developed Quick-Intelligent Handle Evaluation System (QIHES). Moreover, comparisons between the FCE model and subjective evaluation of the FPHCs and total handle valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Sun et al created an MLFE model including tactile comfort and handle features to assess the hand comfort of soft materials and utilised this model to assess the hand comfort of more than 30 fabrics. The outcomes demonstrated that the combination of fullness, stiffness, and roughness determines how well soft textiles work [9].…”
Section: Related Workmentioning
confidence: 99%
“…Sun et al created an MLFE model including tactile comfort and handle features to assess the hand comfort of soft materials and utilised this model to assess the hand comfort of more than 30 fabrics. The outcomes demonstrated that the combination of fullness, stiffness, and roughness determines how well soft textiles work [9].…”
Section: Related Workmentioning
confidence: 99%
“…22,23 The constant weight method has been widely used in the FCE method to determine the weight of each factor. [24][25][26] However, as confirmed in previous studies, the weights of the sensory factors vary based on the different conditions. A few studies have also indicated that in the case in which the value of a specific factor is extremely large, it may play a decisive role in the comprehensive evaluation.…”
mentioning
confidence: 68%
“…Therefore, this paper proposed an experimental test method, the Quick-Intelligent Handle Evaluation System (QIHES), 46,47 and a FE modeling method (geometry, mesh and boundary conditions) composed of the yarn-based fabrics and the finger-based structure of the QIHES to deeply analyze the compression behavior. Meanwhile, the fabric model, based on the cross-sectional size and buckling shape of the yarn characterized by scanning electron microscopy (SEM), and the experimental instrument model involving key component characteristics and performance parameters were built.…”
mentioning
confidence: 99%